Fully Human Anti-CD19 CAR T Cells Derived from Systemic Lupus Erythematosus Patients Exhibit Cytotoxicity with Reduced Inflammatory Cytokine Production - Dingfelder, Janin; Aigner, Michael; Taubmann, Jule; Minopoulou, Ioanna; Park, Soo; Kaplan, Charles D.; Cheng, Joseph K.; Van Blarcom, Tom; Schett, Georg; Mackensen, Andreas; Lutzny-Geier, Gloria (Transplantation and Cellular Therapy, 2024)
KYV-101 is an autologous anti-CD19 chimeric antigen receptor (CAR)-T cell therapy under investigation for patients with B-cell driven autoimmune diseases. Hu19-CD828Z is a fully human anti-CD19 CAR designed and demonstrated to have a favorable clinical safety profile. Since anti-CD19 CAR T cells target and kill B cells in both circulation and tissues, the treatment with Hu19-CD828Z CAR T cells offers great potential in depleting autoreactive B cells. Demonstrate that Hu19-CD828Z CAR T cells manufactured from cryopreserved leukaphereses from patients with systemic lupus erythematosus (SLE) exhibit CAR-mediated and CD19-dependent cytokine release, proliferation and cytotoxicity when co-cultured with autologous primary B cells. T cells were enriched from cryopreserved leukaphereses from SLE patients or healthy donors (HD). CAR T cells were generated by transducing these cells with a lentiviral vector encoding Hu19-CD828Z. CAR-mediated and CD19-dependent activity was monitored in vitro in a set of cytotoxicity, cytokine release, and proliferation studies, in response to autologous primary CD19+ B cells, a CD19+ cell line (NALM-6), or a CD19− cell line (U937). Hu19-CD828Z CAR T cells produced from SLE patients or HD induced greater proliferation and dose-dependent cytotoxicity against both autologous primary B cells and the CD19+ NALM-6 cells than nontransduced control T cells or co-cultures with a CD19− cell line. Interestingly, there was lower inflammatory cytokine production from SLE patient-derived CAR T cells compared to HD donor-derived CAR T cells with either CD19+ cells or primary B cells. Hu19-CD828Z CAR T cells generated from SLE patient lymphocytes demonstrate CAR-mediated and CD19-dependent activity against autologous primary B cells with reduced inflammatory cytokine production supporting KYV-101 as a novel potential therapy for the depletion of pathogenic B cells in SLE patients.
CRIS-Team Scopus Importer:2024-04-19
Keywords: Chimeric antigen receptor; Cytokines; Systemic Lupus Erythematosus